17O NMR spectroscopy as a tool to study hydrogen bonding of cholesterol in lipid bilayers. Issue 92 (5th November 2020) - Rowlands, Lucy J.; Marks, Adam; Sanderson, John M.; Law, Robert V.
Abstract : Solid state NMR of 17 O enriched cholesterol in bilayers reveals the chemical shift depends on extent of hydrogen bonding. Abstract : Cholesterol is a crucial component of biological membranes and can interact with other membrane components through hydrogen bonding. NMR spectroscopy has been used previously to investigate this bonding, however this study represents the first 17 O NMR spectroscopy study of isotopically enriched cholesterol. We demonstrate the 17 O chemical shift is dependent on hydrogen bonding, providing a novel method for the study of cholesterol in bilayers.